The Dilemma of Islamic Parties in the Land of Sharia: A Thematic Analysis of the Bulan Bintang Party in Aceh - Mismaruddin; Marhaban (Journal of Governance and Social Policy, 2025)
This study analyses the campaign strategies and internal evaluation of the Partai Bulan Bintang/PBB in Aceh as a representation of Islamic parties within the local political context. Aceh, with its special autonomy status and the implementation of Islamic law (sharia), theoretically provides opportunities for Islamic parties to gain electoral support. However, election results indicate that PBB has been unable to dominate and tends to lose competitiveness against both national and local parties. Employing a qualitative case study approach, this research is based on in-depth interviews with party officials, legislative candidates, campaign teams, and academics. The findings reveal that PBB’s campaign planning remains focused on formal documents and religious symbols, while the internalization of local values and cadre development has not been optimized. Campaign messages predominantly emphasize sharia issues, strengthening the party’s religious image but limiting its appeal to rational voters. Direct interactions and religious gatherings (pengajian) emerged as the most effective communication channels, whereas the use of social media remains minimal. Internal evaluation highlights key weaknesses, including limited financial resources, weak cadre development, and insufficient support from religious leaders. These findings underscore the need for a balance between traditional and digital strategies, alongside stronger internal consolidation, to enhance PBB’s electoral competitiveness in Aceh